Membangun Fikih yang Berorientasi Sosial: Dialektika Fikih dengan Realitas Empirik Masyarakat - Zubaedi, Z. (Al-Jamiah: Journal of Islamic Studies, 2006)
The present article describes thoughts of what recently called as âsocial fiqhâ, which its substance is an attempt to change qawly paradigm (namely following the sayings of scholars) to manhajy paradigm (following the methodology of scholars). The rise of such idea much concerns with formalistic and legalistic trends of common classical fiqh. The formalistic and legalistic approach to fiqh has encouraged people to manipulate the fiqh and make it separated from ethics as its philosophical base. As the consequence, fiqh becomes rigid and looses its power to provide society with truly effective rules. An epistemological remedy is necessary to break down the rigidity of fiqh and make it powerful to solve social problem.